Nutritional Deficiency and Dental Health: The Role of Phosphorus in Permanent Tooth Eruption - Reno Wiska Wulandari; Nila Kasuma; Fuccy Utami Syafitri; M. Dzaky Sayyid Effendi; Thifla Rafifa Wirza (Open Access Indonesian Journal of Medical Reviews, 2024)
Phosphorus is a vital mineral required for the proper mineralization of bones and teeth, particularly during childhood development. Deficiency in phosphorus intake can lead to delayed dental development, including the eruption of permanent teeth, which may result in oral health complications such as malocclusion and increased risk of dental caries. A cross-sectional study was conducted among 50 children from SD N 15 Koto Lalang, Padang City. Participants were categorized into two groups based on the eruption status of their permanent canines: normal eruption and delayed eruption. Phosphorus intake was measured through dietary surveys, and statistical analysis, including the Mann-Whitney test, was applied to assess the relationship between phosphorus intake and tooth eruption timing. The median phosphorus intake in the normal eruption group was 597.30 mg, significantly higher than the 440.00 mg observed in the delayed eruption group (p = 0.000). The interquartile range (IQR) for the delayed group was narrower, suggesting a more uniform phosphorus deficiency. In conclusion, phosphorus deficiency is a significant factor contributing to delayed eruption of permanent teeth in children. Ensuring adequate phosphorus intake through proper nutrition is crucial for timely dental development and the prevention of long-term oral health issues. Further studies should explore the interaction of phosphorus with other micronutrients to provide a comprehensive understanding of its role in dental health.